Extending the annular in-plane torsional shear test specimen to applications at high strain rates - Osman, Muhsin (Department of Mechanical Engineering, 2022)
The in-plane torsion test is a well-established test used for the characterisation of sheet metals. The specimen is intended to deform in planar simple shear and is designed to be machined with a continuous annular shear zone. As a result, there are no “edge effects” or geometric discontinuities to generate instabilities, thus large true strains up to 1 can be achieved. Before this research, the specimen had only been used for material characterisation in the quasi-static regime. The aim of this research was to conduct further quasi-static testing using the in-plane torsion test and to extend its use into the dynamic regime. Quasi-static tests were performed on a quasi-static torsional (QST) system that was designed to be integrated onto a Zwick universal testing machine. Dynamic tests were performed on a modified torsional split Hopkinson bar (TSHB) system. The TSHB system adopted a nested configuration which allowed for a longer incident bar, and thus larger obtainable strains. Two quick-release mechanisms were used, one using a novel reusable wedge and the other using fracture-pins. All specimens were manufactured from Al 1050 H14. Typical results agreed with material test data available in the literature. Both systems attained large strains at near-constant strain rates and together, allowed for material characterisation over a large range of strain rates. Near-uniform deformations were observed for specimens with lower strain gauge widths. An added feature of the specimen was the flat reverse face, which together with the nested configuration of both systems allows for the possibility for full-field DIC measurement in the future. An estimation method for steady-state flow stress is presented with the steady-state flow stress found to be rate dependant. Finally, a relationship between the steady-state flow stress and strain rate for all experimental results is proposed.